1Malaysia's 'People First, Performance Now': Government public relations in multicultural, multireligious Malaysia - Idid, Syed Arabi; Ahmad, Zeti Azreen (2013)
Numerous efforts have been made by the government to win over the hearts and minds of Malaysians. In this context, public relations oriented efforts have been implemented to promote government’s policies either at the Federal or State level. Some of these programmes are well thought off but others fail in achieving their objectives. However, whatever form these policies or programmes may take, the overriding concern, has been to preserve national unity. The Five Year Development programmes, beginning from the 1957, although socio-economic in approach, take strong cognizance at the fundamental of national integration. The concept of national unity has been taken to the center stage since early independence to the time when Malaysia was formed in 1963 with the unity of Malaya, Sabah and Sarawak. Despite the integration of states, yet one ought to recognize the pull and push of the multicultural, multiracial and multireligious dimensions in Malaysia. This is important in view of the country cultural and social mosaic that comprises of three main ethnic groups; Malay, Chinese and Indian. In Malaysia, Islam is the official religion of the Federation but other faiths are also being practiced e.g., Hinduism, Christianity, Buddhism, Paganism and others.The previous five Prime Ministers of Malaysia had their own concept of national unity. 1Malaysia concept with its catchphrase ‘People First, Performance Now’ is synonymous with the premiership of the current Prime Minister, Dato’ Seri Mohd Najib Tun Abdul Razak. The 1Malaysia concept draws it strength from the contributions of the various races in the running of the government to achieve Vision 2020 and beyond. 1Malaysia is a slogan and a programme to appeal to all Malaysians in winning the support of the multi-ethnic groups in the country. Despite constant criticisms from the opposition parties of it being merely rhetorical, the Malaysian government stays committed to its promise by constantly offering a wide range of 1Malaysian products to meet the immediate needs of the constituents. 1Malaysia is indeed a deliberate government effort to reengineer public consent. At a glance the concept appears no different from the policies introduced by preceding leaders that call for a strong racial unity among the multi-ethnic groups in the country. The study primarily aims to examine the perception of people towards the 1Malaysia concept and its impact in winning their hearts and minds particularly in what was seen as a strategy in securing votes in the recent general election. Besides, it also aims to reflect on how government-publics relationship has transformed since the concept was first launched in 2009 and its ability to curtail social conflicts in Malaysia. This study is part of media and agenda setting project that was initiated since 2009. Data of this study were based from surveys conducted nationwide. The study hopes to offer a better understanding of a unique approach of the public relations efforts of the government in winning public support within Malaysian pluralistic social setting.